Microscopic and submicroscopic infection by Plasmodium falciparum: Immunoglobulin M and A profiles as markers of intensity and exposure - Abad, Paloma; Marín-García, Patricia; Heras, Marcos; Fobil, Julius N.; Hutchful, Alfred G.; Diez, Amalia; Puyet, Antonio; Reyes-Palomares, Armando; Azcárate, Isabel G.; Bautista, José M. (Frontiers in Cellular and Infection Microbiology, 2022)
Assessment of serological Plasmodium falciparum-specific antibodies in highly endemic areas provides valuable information about malaria status and parasite exposure in the population. Although serological evidence of Plasmodium exposure is commonly determined by Plasmodium-specific IgG levels; IgM and IgA are likely markers of malaria status that remain relatively unexplored. Previous studies on IgM and IgA responses have been based on their affinity for single antigens with shortage of immune responses analysis against the whole Plasmodium proteome. Here we provide evidence of how P. falciparum infection triggers the production of specific-IgM and IgA in plasma and its relationship with parasite density and changes in haematological parameters. A total of 201 individuals attending a hospital in Breman Asikuma, Ghana, were recruited into this study. Total and P. falciparum-specific IgM, IgA and IgG were assessed by ELISA and examined in relation to age (0-5, 14-49 and ≥ 50 age ranges); infection (submicroscopic vs. microscopic malaria); pregnancy and haematological parameters. Well-known IgG response was used as baseline control. P. falciparum-specific IgM and IgA levels increased in the population with the age, similarly to IgG. These data confirm that acquired humoral immunity develops by repeated infections through years endorsing IgM and IgA as exposure markers in endemic malaria regions. High levels of specific IgA and IgM in children were associated with microscopic malaria and worse prognosis, since most of them showed severe anaemia. This new finding shows that IgM and IgA may be used as diagnostic markers in this age group. We also found an extremely high prevalence of submicroscopic malaria (46.27% on average) accompanied by IgM and IgA levels indistinguishable from those of uninfected individuals. These data, together with the observed lack of sensitivity of rapid diagnostic tests (RDTs) compared to PCR, invoke the urgent need to implement diagnostic markers for submicroscopic malaria. Overall, this study opens the potential use of P. falciparum-specific IgM and IgA as new serological markers to predict malaria status in children and parasite exposure in endemic populations. The difficulties in finding markers of submicroscopic malaria are highlighted, emphasizing the need to explore this field in depth.